Analysis and Disposal of Forced Power Oscillation in the Transfer Process of Governor Valve Mode of Turbine's Operation. Issue 2 (20th January 2016) - Wang, Jiasheng; Zhong, Jingliang; Zhang, Jie; Wang, Suobin
Abstract: According to a unit's forced power oscillation in the valve mode transfer process, this article presents detailed analysis of the accident and flow changing characteristics of the transfer process, which focuses on the control logic, governor valve characteristic, unit's role in the regional power grid, and so on. Consequently, it is concluded that the large deviation of general valve instruction flow characteristics between single valve mode and sequential valve mode are the main reason for the forced power oscillation, and the unreasonable parameter settings of control systems is a secondary reason. This article presents the concrete anti-measures and puts them into practice. As a result, the transfer of the valve mode of unit's operation is achieved smoothly and successfully without power oscillation between two valve modes, which verify the analysis results. The dynamic process analysis of the transfer is innovative and convincing. Analyzing conclusions and anti-measures are conducive to the stability and safety of power system operation and trouble removal, which also benefit the safety of power grids and units.